Mechanical properties and corrosion resistance of electroless deposited Ni-P-Y2O3 nanocomposite coatings for industrial applications - Muhammad Ahmad; Ahmad Saadi Samra; Sehrish Habib; Ramazan Kahraman; Bilal Mansoor; R. A. Shakoor (Scientific Reports)
Abstract This study investigated the development and corrosion performance evaluation of Ni-P-Y2O3 nanocomposite coatings, synthesized through electroless deposition on A36 carbon steel with varying concentrations of Y2O3 nanoparticles (Y2O3NPs) (0.25 g/L, 0.50 g/L, and 0.75 g/L) within the Ni-P matrix. The incorporation of Y2O3 nanoparticles, along with the innovative use of patent commercialized products solutions Nichem 3010 A and Nichem 3010B where Nichem A and B are commercial electroless plating solutions, which introduces a novel approach to enhancing the corrosion resistance and mechanical properties of the coatings. Structural analyses confirm the formation of phase-pure coatings, with uniform dispersion of Y2O3NPs throughout the Ni-P matrix. Surface topographic analysis reveals an increase in surface roughness in Ni-P-Y2O3 nanocomposite coatings as Y2O3NP concentration increases to 0.75 g/L, attributed to the presence of insoluble and hard Y2O3NPs. Mechanical properties, as evaluated by Vickers microhardness and nanoindentation tests, demonstrated a marked improvement in hardness, with Y2O3NP (0.75 g/L) incorporation proved to have the highest microhardness (764.7Hv) and elastic modulus (6.52GPa), suggesting a synergistic enhancement due to grain refinement and dispersion effects. Electrochemical assessments, including Tafel analysis and Electrochemical Impedance Spectroscopy (EIS), reveal that incorporating 0.75 g/L of Y2O3NPs into the Ni-P structure significantly reduces the corrosion current density (icorr) while increasing polarization resistance (Rp) in comparison to other concentrations (0.25 g/L and 0.50 g/L). This result indicates superior corrosion resistance, with the Ni-P-Y2O3 nanocomposite coatings exhibiting an impressive corrosion resistance improvement of 82.76%. This enhanced resistance is attributed to the mechanism whereby Y2O3NPs occupy micropores, thereby reducing active corrosion sites within the Ni-P matrix. The findings strongly suggest that Ni-P-Y2O3 composite coatings offer a robust solution for corrosion mitigation, presenting them as promising candidates for application in aggressive and corrosive environments.